Northlands : New Art from Scandinavia (Oxford : Museum of Modern Art, 1990)
Aih, Martti ; Breivik, Bard ; Gudmundsson, Kristján ; Jenssen, Olav Christopher ; Klarskov Jorgensen, Elle ; Mäkelä, Mariko ; Nilsson, Lars ; Orfali, Ingrid ; Oskar, Jon ; Stokke, Bente ; Wörsel, Troels
Northlands : New Art from Scandinavia, The Museum of Modern Art, Oxford ; The Nordic ARts Centre, Helsinki, 1990
boek
Keywords: Scandinavië